A Comparison of Learning Styles with Student Comfort and Satisfaction in Online and Traditional Learning Environments - Gerri Hura (Adult Education Research Conference, 2007)
This study looked at students’ learning styles and their comfort and satisfaction with traditional and online learning environments. The purpose was to determine the impact learning styles and age have on student comfort and satisfaction for a graduate population.